The Investigation of Astaxanthin Effect on Fatty Acid Values in Liver and Kidney Tissues of Rats which Exposed to Nicotine - Dayangac, Alpaslan; Akkoyun, H. Turan; Aydin, Sevinc; Akkoyun, Mahire Bayramoglu; Bahsi, Muammer; Akbas, Gulistan; Yilmaz, Okkes (Wiley-Blackwell, 2015)
[Abstract Not Available]